A Proposed Solution to The Linguistic Relativity (Sapir–Whorf) Hypothesis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The question of whether human language plays a constitutive role in shaping human thought, or merely dresses up pre-formed thoughts—thus occupying a secondary role in the constitution of thought—has occupied scientists and philosophers of language and mind for centuries. The present paper undertakes a philosophical investigation of the Sapir–Whorf hypothesis and seeks to dispel certain confusions surrounding it. It is demonstrated that human language is both an inseparable component of human psychology (a cognitive mechanism) and an indispensable part of the social practices in which humans participate (a social tool, a technology that each culture uses creatively). The distinction between language as a cognitive–semiotic system and as a culture specific-national constituent is crucial when we investigate linguistic relativity. Ultimately, language coordinates, influences, and directs thought and psychological processes; it also constitutes and reproduces culture, helping it to evolve.